Joint Clustering and Routing Optimisation for Low-power Wireless Sensor Networks - Le Viet, Thanh; Bui, Minh-Phung; Phan, Thanh-Minh; Tran, Thanh-Dung (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2023)
Wireless sensor networks (WSNs) have been one of the fields that have attracted a lot of attentions from many scientific researchers in recent years. The sensor nodes of the network are fixed or moved to detect the environment and impart the data accumulated from the remote monitored regions via wireless connections. It is indicated in complex environments such as forests, deep seas, urban areas, etc., the sensor nodes in WSNs are usually tiny and battery-driven devices. Thus, energy-effective data accumulation methods required to improve the network’s lifetime are very necessary. In this paper, we propose a joint technique of fuzzy clustering and heuristic ant routing (FCHAR) to save the energy for low-power WSNs. Simulation results are shown to demonstrate the benefits of the proposed FCHAR compared to other conventional ones.
Keywords: Ant Colony Optimization; fuzzy clustering; heuristic routing; wireless sensor networks